Impact of maternal anaemia on cord blood haemoglobin - Ramadoss, Dhanasekaran; Arumugam, Sumitha; ., Suguna (International Journal of Contemporary Pediatrics, 2019)
Background: Anaemia during pregnancy is associated with serious maternal and fetal complications. Cord blood hemoglobin of the newborn is an important indicator of anaemia in newborn at birth. So, this study is done to assess the impact of maternal anaemia on cord blood hemoglobin levels of neonates. Methods: It is a cross sectional study done at government Kilpauk medical college and hospital in the department of paediatrics in year 2016.400 pregnant mothers attending the labour room in Kilpauk medical college were included and cord blood haemoglobin of their babies were collected. Mean cord blood haemoglobin of new-borns born to anaemic mothers (mild, moderate and severe) were compared with cord blood haemoglobin of new-borns born to non-anaemic mothers. Results: Out of 400 mothers,192 mothers were anemic, and 208 mothers were non anemic. The mean maternal hemoglobin among non-anemic mothers was 16.37±0.85 and among the anemic mothers it was 15.03±1.04. The mean cord hemoglobin of neonates born to anemic mothers among the three groups (mild moderate severe) were compared with mean cord hemoglobin of the non-anemic group. The difference between groups were statistically significant with P values <0.05,0.01 and 0.05 respectively. Conclusions: In present study maternal anaemia affects the cord blood haemoglobin of neonates. Present study infers that anaemic mothers deliver babies with lower haemoglobin compared to non-anaemic mothers. Authors have found a linear relationship between maternal haemoglobin and cord blood haemoglobin of the new-borns.